COVID-19 and HELLP: Overlapping Clinical Pictures in Two Gravid Patients - Itamar Futterman; Miriam Toaff; Liel Navi; Camille A. Clare (Thieme Medical Publishers, Inc., 2020)
Background The impact of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) on pregnancies is currently under investigation. There is a significant overlap between the clinical findings in novel coronavirus disease 2019 (COVID-19) and hemolysis, elevated liver enzymes, and low platelets syndrome (HELLP). Cases Patients presented at 22 and 29 weeks of gestation with suspected COVID-19 pneumonia. While the patient at 22 weeks of gestation subsequently had an intrauterine fetal demise, the patient at 29 weeks of gestation delivered via an emergency cesarean delivery for nonreassuring fetal status. Both patients also developed transaminitis, thrombocytopenia, and disseminated intravascular coagulation with a proof of hemolysis on peripheral smear. Conclusion Clinicians are encouraged to consider both of these diagnoses when caring for pregnant women during the COVID-19 pandemic to assure that both maternal and fetal concerns are addressed and treated appropriately.